2021
DOI: 10.1002/ente.202100676
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Polymer Reflectors for Organic Solar Cells

Abstract: Due to their high transparency, electrodes fabricated from conductive polymers are often implemented in semitransparent organic solar cells. Opaque solar cells usually employ metal back electrodes with high reflectivity for best photon confinement in the light‐harvesting layer. Herein, a bilayer back electrode comprising conductive polymers and nanofoamed poly(methyl methacrylate) (PMMA) is investigated, the latter of which creates diffuse reflection of the incoming light. By tuning the thickness of the nanofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…By varying the thickness of pristine polymer film, different reflectance can be obtained, which is desired for the light management of semi‐transparent OSCs. [ 36 ] At last, a 50 µm‐thick foamed polymer film can increase the PCE of OSCs from 5.9% to 6.8%, comparable with the highly reflective silver electrode. Detailed characterizations showed that the PCE enhancement was attributed to the increased light absorption in the low‐absorbing spectral range and further improved photocurrent in the OSCs.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…By varying the thickness of pristine polymer film, different reflectance can be obtained, which is desired for the light management of semi‐transparent OSCs. [ 36 ] At last, a 50 µm‐thick foamed polymer film can increase the PCE of OSCs from 5.9% to 6.8%, comparable with the highly reflective silver electrode. Detailed characterizations showed that the PCE enhancement was attributed to the increased light absorption in the low‐absorbing spectral range and further improved photocurrent in the OSCs.…”
Section: Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [ 36 ] Copyright 2021, The Authors, published by Wiley‐VCH. Porous polymers are also excellent candidates applied in the passive daytime radiative cooling [ 37 ] and radiative cooling fabrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric scatterer based on titania can be used to redirect light in stacked homo- 212 and hetero- 213 tandem devices based on semitransparent 212 215 OPV devices, converting the semitransparent OPV to an opaque OPV. With white paper 216 or nanoporous polymers, 217 as well as a microstructured retroreflector, 218 light harvesting is improved.…”
Section: Organic Pvmentioning
confidence: 99%
“…Besides the enhancement in charge transport layers, the incorporation in the electrode has also been recently demonstrated a promising approach to replace commonly used metals. Yu et al 160 showcased a highly reflective nanoporous polymer incorporated back electrode with thickness-dependent opacity and transmission. Through CO 2 diffusion, the nanofoamed PMMA presents an excellent reflectance profile compared to the silver electrode in the Vis-NIR region.…”
Section: Pop-based Organic Solar Cells (Opv)mentioning
confidence: 99%